This is not an Arena for Party Leaders: Presidential Elections in the 3rd Republic of Poland - Pieniężny Dawid (Politics in Central Europe, 2025)
Next to parliamentary elections, presidential elections in Poland are regarded as the key arena of political competition in Poland. On the one hand, the specific nature of the political system dictates that the significant, albeit negative, role of the head of state in shaping the law and the President’s relatively broad prerogatives regarding the conduct of public business as compared to the standards of the parliamentary-cabinet system should be pointed out. On the other hand, the limitation of the real power of the President compared to the position of the Prime Minister does not provide an incentive for the leaders of the key political parties in Poland to abandon the struggle for the position of the head of government in favour of the presidency. This text addresses the issue of the nomination of candidates for the analysed office, attempting to answer the question of why it is not the party leaders who face off against each other, but rather the arena of competition between candidates from the second row of party structures. Conclusions from the case study suggest that the reasons for this are that party leaders, burdened by the negative consequences of political power, fear that they will not be able to surpass the ‘glass ceiling’ of party support. Thus, they fear that they will not only suffer a personal loss, but reckon with the consequences for the party as a whole. For each of the main parties, fielding a different candidate is seen as an opportunity to reach beyond the committed party electorate and escape the high negative sentiment around each of the two main leaders.